Method for manufacturing substrate with wiring electrode
By transferring the positive photosensitive resin layer on the opaque wiring electrode pattern and using it as a mask for exposure, the problem of increasing exposure amount and development time caused by light shading laminar leveling is solved, and efficient light shading layer formation and visual concealment are achieved. Effect.
Patent Information
- Application Number
- CN202380033942.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-04-10
- Publication Date
- 2024-12-20
AI Technical Summary
When forming a light shielding layer, the light shielding layer is also formed in the opaque wiring electrode due to the flow level of the positive photosensitive light shielding composition, which increases the exposure amount and development time, and easily leads to deterioration and peeling of the developing film, affecting visual concealment. Effect.
By transferring the positive photosensitive resin layer containing the light-shielding component to the opaque wiring electrode pattern forming surface, a light-shielding layer is formed, and exposure and development is performed using the opaque wiring electrode as a mask, ensuring that the light-shielding layer is formed only at the required parts, and solving the problem of Leveling problem.
The efficient concealment of the opaque wiring electrode pattern is achieved, the development time and exposure amount are reduced, the processability and visual concealment effect are improved, and the damage to the developing film is avoided.
Smart Images

Figure CN119173814A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a substrate with wiring electrodes, which has an opaque wiring electrode pattern and a light shielding pattern on at least one surface of a transparent substrate. Background Art
[0002] In recent years, the touch panel widely used as an input means is composed of a display unit such as a liquid crystal panel, and a touch panel sensor for detecting information input to a specific position. As the wiring electrode used in the touch panel sensor, a transparent wiring electrode is usually used from the viewpoint that the wiring electrode is not easy to see, but in recent years, due to high sensitivity and large screens, opaque wiring electrodes using metal materials have been widely used. There is a problem that the opaque wiring electrode using metal materials is visually recognized due to the metallic luster. Therefore, as a method for not being able to visually recognize the opaque wiring electrode, a method for manufacturing a substrate with a wiring electrode is proposed, which has: a process of forming an opaque wiring electrode on at least one side of a transparent substrate; a process of applying a positive photosensitive light-shielding composition on one side of the aforementioned transparent substrate; and a process of exposing the aforementioned positive photosensitive composition using the aforementioned opaque wiring electrode as a mask and developing it, thereby forming a light-shielding layer at a position corresponding to the opaque wiring electrode (for example, see patent document 1).
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: International Publication No. 2018 / 168325 Summary of the invention
[0006] Problems to be solved by the invention
[0007] By using the manufacturing method described in Patent Document 1, a substrate with wiring electrodes having fine patterns, excellent conductivity, and in which opaque wiring electrodes and wiring electrodes are not easily visually recognizable can be obtained. However, if a positive-type photosensitive light-shielding composition is applied to the opaque wiring electrode when forming a light-shielding layer, a positive-type photosensitive light-shielding composition layer is also formed in a portion where there is no opaque wiring electrode due to leveling. Therefore, relative to the thickness of the light-shielding layer formed on the opaque wiring electrode, the thickness of the portion to be removed by the photolithography process becomes larger. As a result, there are problems in terms of processability, such as an increase in the amount of exposure required for pattern formation of the light-shielding layer and a prolonged development time. In addition, as the development time becomes longer, there are problems such as easy loss of the developing film, development peeling, and easy visual recognition of the opaque wiring electrode.
[0008] Therefore, an object of the present invention is to provide a method for producing a substrate with wiring electrodes which is excellent in processability and in which an opaque wiring electrode pattern is not easily visually recognized.
[0009] Means for solving problems
[0010] In order to solve the above-mentioned problems, the present invention mainly has the following configurations.
[0011] <1> A method for manufacturing a substrate with wiring electrodes, comprising:
[0012] forming an opaque wiring electrode pattern on at least one surface of a transparent substrate;
[0013] a step of forming a light shielding layer by transferring a positive photosensitive resin layer containing a light shielding component to the opaque wiring electrode pattern forming surface of the transparent substrate; and
[0014] The light shielding layer is exposed to light using the opaque wiring electrode pattern as a mask and then developed to form a light shielding pattern at a portion corresponding to the opaque wiring electrode pattern.
[0015] <2> The method for producing a substrate with wiring electrodes according to <1>, wherein the thickness T1 [μm] of the positive photosensitive resin layer is 0.3 to 2.0.
[0016] <3> A method for manufacturing a substrate with wiring electrodes as described in <1> or <2>, wherein the total of the thickness T1 [μm] of the positive photosensitive resin layer and the thickness T2 [μm] of the opaque wiring electrode pattern is 1.5 to 10.0, and T1 and T2 satisfy the following formula (1).
[0017] 0.1 <T1 / (T1+T2)<0.5 (1)
[0018] <4> The method for producing a substrate with wiring electrodes according to any one of <1> to <3>, wherein a thickness T2 [μm] of the opaque wiring electrode pattern is 1.0 to 5.0.
[0019] <5> The method for producing a substrate with wiring electrodes according to any one of <1> to <4>, wherein the positive photosensitive resin layer contains (b-1) an acrylic resin having a phenolic hydroxyl group and a carboxyl group.
[0020] <6> The method for producing a substrate with wiring electrodes according to <5>, wherein the positive photosensitive resin layer further contains (b-2) phenol novolac resin.
[0021] <7> A method for manufacturing a substrate with wiring electrodes as described in <6>, wherein the mass ratio ((b-1) / (b-2)) of the content of the aforementioned (b-1) acrylic resin having phenolic hydroxyl groups and carboxyl groups in the aforementioned positive photosensitive resin layer to the content of the aforementioned (b-2) phenol Novolac resin is greater than 1.0 and less than 3.0.
[0022] <8> The method for producing a substrate with wiring electrodes according to any one of <1> to <7>, wherein a line width of the opaque wiring electrode pattern is 1 to 10 μm.
[0023] <9> A method for manufacturing a substrate with wiring electrodes as described in any one of <1> to <8>, wherein the aforementioned substrate with wiring electrodes has at least a fine line pattern portion, and in the fine line pattern portion, the ratio of the area where the aforementioned opaque wiring electrode pattern is formed relative to the aforementioned transparent substrate as a whole is less than 20 area%.
[0024] <10> The method for producing a substrate with wiring electrodes according to any one of <1> to <9>, wherein the light transmittance of the opaque wiring electrode pattern at a wavelength of 365 nm is 15% or less.
[0025] <11> The method for producing a substrate with wiring electrodes according to any one of <1> to <10>, wherein the opaque wiring electrode pattern contains silver and / or copper.
[0026] Effects of the Invention
[0027] According to the present invention, a substrate with wiring electrodes in which an opaque wiring electrode pattern is not easily visible can be obtained with good processability. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] [ Figure 1 ] is a schematic diagram showing an example of the structure of a substrate with wiring electrodes in the present invention.
[0029] [ Figure 2 ] is a schematic diagram showing another example of the structure of the substrate with wiring electrodes in the present invention.
[0030] [ Figure 3 ] is a schematic diagram showing a portion of an example of a method for manufacturing a substrate with wiring electrodes according to the present invention.
[0031] [ Figure 4 ] is a schematic diagram showing the electrode pattern used in the embodiments and comparative examples for evaluating visual recognition and conductivity.
[0032] [ Figure 5 ] is a schematic diagram of the grid pattern of the negative mask used in the embodiments and comparative examples.
[0033] [ Figure 6 ] is a schematic diagram of the grid pattern of the positive mask used in the embodiments and comparative examples. DETAILED DESCRIPTION
[0034] The substrate with wiring electrodes in the present invention has an opaque wiring electrode pattern on at least one side of the transparent substrate, and has a shading pattern in the portion corresponding to the opaque wiring electrode pattern. The shading pattern has the effect of making the opaque wiring electrode pattern difficult to be visually recognized. In addition, an overcoat may be provided on them. By having the overcoat, the surface of the opaque wiring electrode pattern and the shading pattern can be protected, and damage can be suppressed. It should be noted that in the present invention, a shading pattern may be provided in a portion of the portion corresponding to the opaque wiring electrode pattern. For example, in the case of a substrate with wiring electrodes used in a touch panel sensor, it is required that the opaque wiring electrode pattern is not easily visually recognized in a display portion such as a liquid crystal panel, and therefore it is preferred to have a shading pattern in the display portion.
[0035] Figure 1 A schematic diagram showing an example of the structure of a substrate with wiring electrodes in the present invention is shown. An opaque wiring electrode pattern 2 is provided on a transparent substrate 1, and a light shielding pattern 3 is provided on the opaque wiring electrode pattern 2. Figure 2 Another example of the structure of the substrate with wiring electrodes in the present invention is shown. An opaque wiring electrode pattern 2 (first opaque wiring electrode pattern) and an insulating layer 4 are provided on a transparent substrate 1, an opaque wiring electrode pattern 2 (second opaque wiring electrode pattern) is provided on the insulating layer 4, and a light shielding pattern 3 is provided at a portion corresponding to the opaque wiring electrode pattern 2 (first opaque wiring electrode pattern and second opaque wiring electrode pattern).
[0036] The manufacturing method of the substrate with wiring electrodes of the present invention comprises: a step of forming an opaque wiring electrode pattern on at least one side of a transparent substrate (hereinafter, sometimes referred to as an "opaque wiring electrode pattern forming step"); a step of forming a light-shielding layer by transferring a positive photosensitive resin layer containing a light-shielding component to the opaque wiring electrode pattern forming surface of the transparent substrate (hereinafter, sometimes referred to as a "light-shielding layer forming step"); and a step of exposing and developing the light-shielding layer using the opaque wiring electrode pattern as a mask, thereby forming a light-shielding pattern at a portion corresponding to the opaque wiring electrode pattern (hereinafter, sometimes referred to as a "light-shielding pattern forming step"). The light-shielding layer is formed on the surface on which the opaque wiring electrode pattern is formed by the opaque wiring electrode pattern forming step, and the light-shielding layer is exposed and developed using the opaque wiring electrode pattern as a mask, thereby forming a light-shielding pattern at a portion corresponding to the opaque wiring electrode pattern. Here, if a positive photosensitive light-shielding composition is applied to a surface with a concave and convex surface on which an opaque wiring electrode pattern is formed on a transparent substrate in the light-shielding layer forming process, then as described above, the positive photosensitive light-shielding composition is applied not only to the convex part but also to the concave part due to leveling, and a light-shielding layer is also formed in a part without an opaque wiring electrode pattern. In this part, a light-shielding layer is also formed with the thickness of the originally planned light-shielding layer plus the amount equivalent to the thickness of the opaque wiring electrode pattern, and there is a tendency for the exposure amount and development time required for pattern formation to increase, and there is a problem in processability. If the development time becomes longer, it is easy to cause the development film to be damaged and the development peeling, the effect of the light-shielding layer is reduced, and there is a problem of easy visual recognition of the opaque wiring electrode pattern. From the perspective of conductivity, the thicker the thickness of the opaque wiring electrode pattern is, the more significant this problem is. In view of this, the present invention is characterized in that, in the light-shielding layer forming process, a positive photosensitive resin layer with morphological retention is transferred. By transferring the positive photosensitive resin layer to form the light shielding layer, the above-mentioned problem caused by leveling can be solved, and the light shielding layer with a desired thickness can be formed with good processability, and the opaque wiring electrode pattern can be less easily visually recognized.
[0037] Figure 3 , as a part of an example of a method for manufacturing a substrate with wiring electrodes of the present invention, a schematic diagram of an exposure process of a light shielding layer in a light shielding pattern forming process is shown. An opaque wiring electrode pattern 2 is formed on one side of a transparent substrate 1, and a positive photosensitive resin layer containing a light shielding component is transferred thereon, thereby forming a light shielding layer 5. Exposure is performed from the side opposite to the surface of the transparent substrate 1 on which the opaque wiring electrode pattern 2 is formed, thereby enabling the light shielding layer 5 to be exposed using the opaque wiring electrode pattern 2 as a mask.
[0038] Each process is described.
[0039] First, in the opaque wiring electrode pattern forming step, an opaque wiring electrode pattern is formed on at least one side of a transparent substrate. The opaque wiring electrode pattern may also be formed on both sides of the transparent substrate. Here, "transparent" means that the transmittance at a wavelength of 550nm is 50% or more, and "opaque" means that the transmittance at a wavelength of 550nm is less than 50%. It should be noted that the transmittance at a wavelength of 550nm can be measured using an ultraviolet visible spectrophotometer (U-3310: manufactured by Hitachi High-Technologies).
[0040] The opaque wiring electrode pattern preferably has a fine line pattern formed by a pattern with a line width of less than 20 μm. It is more preferable to have a fine line pattern and a pad portion. Here, the pad portion refers to a portion electrically connected to an external element, and is usually formed in a portion that is not visually recognizable. For example, in the case of a substrate with wiring electrodes used in a touch panel sensor, in order to detect a touch position, the opaque wiring electrode pattern has a fine line pattern at a position corresponding to a display portion such as a liquid crystal panel, and in order to be electrically connected to an external element, it is preferred to have a pad portion outside the display portion. In addition, outside the display portion, there may be a detour wiring for connecting these fine line patterns to the pad portion. It should be noted that in the present invention, as described above, it is preferred to have a shading pattern in the display portion, and therefore it is preferred to have a shading pattern in a portion corresponding to the fine line pattern, and there may be no shading pattern in a portion corresponding to the opaque wiring electrode pattern in a non-display portion such as a pad portion and a detour wiring.
[0041] The transparent substrate is preferably transmissive to the exposure light used in the shading pattern forming step described later. Specifically, the light transmittance at a wavelength of 365 nm is preferably 50% or more, and more preferably 70% or more. By setting the light transmittance at a wavelength of 365 nm to be 50% or more, the positive photosensitive composition can be efficiently exposed in the shading pattern forming step described later. It should be noted that the light transmittance of the transparent substrate at a wavelength of 365 nm can be measured using an ultraviolet visible spectrophotometer (U-3310: manufactured by Hitachi High-Technologies).
[0042] The transparent substrate may be flexible or inflexible. As a transparent substrate without flexibility, for example, a quartz glass substrate, a soda-lime glass substrate, an alkali-free glass substrate, a chemically reinforced glass substrate, a "Pyrex (registered trademark)" glass substrate, a synthetic quartz plate, an epoxy resin substrate, a polyetherimide resin substrate, a polyetherketone resin substrate, a polysulfone resin substrate, etc. can be cited. As a transparent substrate with flexibility, for example, resin films such as polyethylene terephthalate film (hereinafter, denoted as "PET film"), cycloolefin polymer film, polyimide film, polyester film, aramid film, optical resin plate, etc. can be cited. These can be overlapped and used in plurality, for example, a plurality of transparent substrates can also be bonded together using an adhesive layer. In addition, an insulating layer can be provided on the surface of these transparent substrates.
[0043] The thickness of the transparent substrate is appropriately selected according to the material within the range of being able to stably support the opaque wiring electrode pattern and having the aforementioned transmittance. For example, from the viewpoint of more stably supporting the opaque wiring electrode pattern, in the case of a non-flexible transparent substrate, the thickness of the transparent substrate is preferably 0.3 mm or more, and in the case of a flexible transparent substrate, the thickness of the transparent substrate is preferably 25 μm or more. On the other hand, from the viewpoint of further improving the transmittance of the exposure light, in the case of a non-flexible transparent substrate, the thickness of the transparent substrate is preferably 1.5 mm or less, and in the case of a flexible transparent substrate, the thickness of the transparent substrate is preferably 300 μm or less.
[0044] The light transmittance of the opaque wiring electrode pattern at a wavelength of 550nm is preferably 25% or less. In addition, the opaque wiring electrode pattern preferably has a light shielding property against the exposure light used in the light shielding pattern forming process described later. Specifically, the light transmittance of the opaque wiring electrode pattern at a wavelength of 365nm is preferably 15% or less. By setting the light transmittance at a wavelength of 365nm to be 15% or less, the function as a mask in the light shielding pattern forming process described later is improved, and the desired light shielding pattern can be formed with better processability. The light transmittance of the opaque wiring electrode pattern at a wavelength of 365nm is more preferably 5% or less, and further preferably 3% or less. In the case where a light shielding pattern is formed in a portion of the portion corresponding to the opaque wiring electrode pattern, the light transmittance of the opaque wiring electrode pattern in the portion where the light shielding pattern is formed is preferably within the above range, and the light transmittance of the fine line pattern in the opaque wiring electrode pattern is preferably within the above range. The light transmittance of the opaque wiring electrode pattern can be measured using a micro-spectrophotometer (VSS 400: manufactured by Nippon Denshoku Industries, Ltd.) for an opaque wiring electrode pattern having a size of 0.1 mm square or more.
[0045] As the material constituting the opaque wiring electrode pattern, for example, conductive materials such as metals such as silver, gold, copper, platinum, lead, tin, nickel, aluminum, tungsten, molybdenum, chromium, titanium, and indium, and alloys thereof can be cited. Two or more of these can be used. Among these, silver, copper, and the like are preferred from the viewpoint of conductivity.
[0046] As a raw material used in the formation of the opaque wiring electrode pattern, conductive particles containing the aforementioned conductive material are preferably spherical in shape. From the viewpoint of improving the dispersibility of the conductive particles, the average particle size of the conductive particles is preferably 0.03 μm or more. On the other hand, from the viewpoint of making the end of the pattern of the opaque wiring electrode sharp, the average particle size of the conductive particles is preferably 1.0 μm or less. It should be noted that the average particle size of the conductive particles can be obtained by the following method: using a scanning electron microscope (SEM) or a transmission microscope (TEM), the conductive particles are magnified and observed at a magnification of 15,000 times, and for 100 randomly selected conductive particles, the length of each major axis is measured, and the number average is calculated.
[0047] The opaque wiring electrode pattern may contain the aforementioned conductive material and an organic component. The opaque wiring electrode pattern may be formed, for example, from a cured product of a photosensitive conductive composition containing conductive particles, an alkali-soluble resin, and a photopolymerization initiator. In this case, the opaque wiring electrode pattern contains a photopolymerization initiator and / or a photodegradable product thereof. The photosensitive conductive composition may contain additives such as a thermosetting agent and a leveling agent as required.
[0048] As the shape of the fine line pattern in the opaque wiring electrode pattern, for example, a grid shape, a stripe shape, etc. can be cited. As the grid shape, for example, a grid shape in which the unit shape is a triangle, a quadrilateral, a polygon, a circle, etc. or a grid shape formed by a combination of these unit shapes can be cited. Among these, a grid shape is preferred from the viewpoint of making the conductivity of the pattern uniform. The fine line pattern in the opaque wiring electrode pattern is more preferably a metal grid composed of the aforementioned metal and having a grid pattern.
[0049] From the viewpoint of improving conductivity, the thickness T2 [μm] of the opaque wiring electrode pattern is preferably greater than 0.5, more preferably greater than 1.0, and further preferably greater than 1.5. On the other hand, from the viewpoint of forming finer wiring, the thickness T2 [μm] of the opaque wiring electrode pattern is preferably less than 10, more preferably less than 5.0, and further preferably less than 3.0. In addition, in the case where the substrate with the wiring electrode has an outer covering layer, by making the thickness T2 [μm] of the opaque wiring electrode pattern less than 10, the uneven step difference on the transparent substrate can be reduced, and the generation of bubbles caused by the step difference when the outer covering layer is stacked can be suppressed. The thickness of the fine line pattern in the opaque wiring electrode pattern is preferably within the above range. It should be noted that the thickness T2 [μm] of the opaque wiring electrode pattern can be obtained by the following method: for 5 randomly selected locations, the thickness is measured using a stylus step difference meter "SURFCOM" (registered trademark) 1400 (manufactured by Tokyo Seimitsu Co., Ltd.), and the average value is calculated.
[0050] From the viewpoint of improving conductivity, the line width of the pattern of the opaque wiring electrode is preferably greater than 1 μm, more preferably greater than 1.5 μm, and further preferably greater than 2 μm. On the other hand, from the viewpoint of making it more difficult to visually identify the wiring electrode, the line width of the pattern of the opaque wiring electrode is preferably less than 10 μm, more preferably less than 8 μm. The line width of the fine line pattern in the opaque wiring electrode pattern is preferably within the above range. It should be noted that the line width of the pattern of the opaque wiring electrode can be obtained by measuring 5 randomly selected locations using an optical microscope and calculating the average value.
[0051] In the case where the opaque wiring electrode pattern has a fine line pattern, from the viewpoint of making the opaque wiring electrode pattern less visually recognizable, in the portion of the substrate with wiring electrodes where the fine line pattern is formed (the fine line pattern portion), the proportion of the area where the opaque wiring electrode pattern is formed relative to the transparent substrate as a whole is preferably 20% by area or less, and more preferably 15% by area or less. The opaque wiring electrode pattern can be stacked in two or more layers via a transparent protective layer. In particular, by stacking the fine line pattern, the proportion of the area where the fine line pattern is formed can be reduced while maintaining conductivity, making it less visually recognizable. It should be noted that the area where the fine line pattern is formed can be calculated by measuring the length and width of the fine line pattern using an optical microscope.
[0052] The opaque wiring electrode pattern forming process may include: a process of forming a first opaque wiring electrode pattern on a single surface of a transparent substrate; a process of forming an insulating layer on the aforementioned first opaque wiring electrode; and a process of forming a second opaque wiring electrode pattern on the aforementioned insulating layer.
[0053] As a method for forming an opaque wiring electrode pattern, for example, there can be cited: a method of forming a pattern by photolithography using the aforementioned photosensitive conductive composition; a method of forming a pattern by screen printing, gravure printing, inkjet, etc. using a conductive composition (conductive paste); a method of forming a film of metal, metal composite, metal and metal compound composite, metal alloy, etc., using a resist, and forming a pattern by photolithography; etc. It should be noted that in the case of forming an opaque wiring electrode pattern on both sides of a transparent substrate, in the case of forming more than two layers of opaque wiring electrode patterns through an insulating layer, and in the case of forming a fine line pattern and other patterns by different processes, each opaque wiring electrode pattern can be formed by the same method, or different methods can be combined. An insulating layer can be formed on the opaque wiring electrode pattern of the substrate with the obtained opaque wiring electrode pattern. As an insulating layer and a method for forming the same, for example, the insulating layer and the method for forming the same as exemplified in International Publication No. 2018 / 168325 can be cited.
[0054] Next, in the light-shielding layer forming process, a positive photosensitive resin layer containing a light-shielding component is transferred to the opaque wiring electrode pattern forming surface of the transparent substrate to form a light-shielding layer. As a positive photosensitive resin layer, for example, a so-called dry film obtained by the following method can be used: a positive photosensitive resin composition containing a light-shielding component is coated on a release film and dried as needed. By transferring a positive photosensitive resin layer having a morphological retention property such as a dry film, the aforementioned problems caused by leveling can be solved, and a light-shielding layer of a desired thickness can be formed with good processability, so that the opaque wiring electrode pattern can be difficult to be visually recognized. As a dry film, it is preferred to use a black transfer film described later. Below, the light-shielding layer forming process using a dry film is described as an example.
[0055] First, a dry film is prepared. A positive photosensitive resin composition containing a light-shielding component is applied onto a release film and then dried to produce a dry film having a positive photosensitive resin layer containing a light-shielding component.
[0056] The term "releasable film" refers to a film having a release layer on the surface.
[0057] As the release agent for forming the release layer, for example, non-silicone release agents and silicone release agents can be cited. As the non-silicone release agent, for example, long-chain alkyl release agents, fluorine release agents, etc. can be cited. Two or more of them can be used. Among these, even if the release agent transfers during transfer, it is not easy to repel the developer in the subsequent steps, especially the development step, and it can suppress the unevenness in the surface to form a fine pattern. Considering that the thickness of the release layer is preferably 50nm or more from the viewpoint of suppressing the transfer unevenness during transfer. On the other hand, from the viewpoint of suppressing the transfer of the release agent during transfer, the thickness of the release layer is preferably 500nm or less.
[0058] From the viewpoint of suppressing repulsion during the formation of the positive photosensitive resin layer, the peeling force of the release film is preferably 500mN / 20mm or more. On the other hand, from the viewpoint of expanding the process margin during the transfer of the positive photosensitive resin layer, the peeling force of the release film is preferably 5,000mN / 20mm or less. Here, the peeling force of the release film refers to the peeling force when the acrylic adhesive tape "31B" manufactured by Nitto Denko Co., Ltd. is adhered to the surface formed by the release layer using a 2kg roller, and after standing for 30 minutes, it is peeled off at a peeling angle of 180° and a peeling speed of 0.3m / min.
[0059] As the film used in the release film, for example, films containing resins such as polyethylene terephthalate (PET), cycloolefin polymers, polycarbonates, polyimides, aromatic polyamides, fluororesins, acrylic resins, and polyurethane resins can be cited. Two or more of them can be used. Among these, it is preferred to have a film that is transmissive to the exposure light used in the shading pattern forming process described later, preferably a film containing PET, cycloolefin polymers, and polycarbonate. By selecting a film that is transmissive to the exposure light, it is possible to expose through the release film in the shading pattern forming process described later. In this case, by placing the release film between the positive photosensitive resin layer and the photomask, contamination of the photomask can be suppressed.
[0060] From the viewpoint of improving the handling stability during the formation of the positive photosensitive resin layer and suppressing the uneven thickness of the positive photosensitive resin layer, the thickness of the release film is preferably 5 μm or more, and more preferably 10 μm or more. On the other hand, from the viewpoint of the operability during peeling, the thickness of the release film is preferably 300 μm or less, and more preferably 200 μm or less.
[0061] As the light-shielding component, for example, dyes, organic pigments, inorganic pigments, etc. can be cited. Two or more of them can be contained. More specifically, for example, substances exemplified as colorants in International Publication No. 2018 / 168325, soluble azo pigments, insoluble azo pigments, metal complex salt azo pigments, phthalocyanine pigments, organic pigments such as condensed polycyclic pigments, pine smoke, ultramarine, iron black, hematite, goethite, magnetite and other iron oxides, titanium, chromium, lead, and their metal composites can be cited. Two or more of them can be used. Among these, carbon black is preferred from the viewpoint of ease of acquisition, and titanium nitride is preferred from the viewpoint of the transmittance of exposure light.
[0062] The content of the light-shielding component in the positive photosensitive resin layer is preferably 5 to 30% by mass.
[0063] The so-called positive photosensitive resin composition refers to a composition having positive photosensitivity in which the light-irradiated portion dissolves in a developer, and preferably contains a photosensitizer (dissolution inhibitor) and an alkali-soluble resin. In addition, a plasticizer, a leveling agent, a surfactant, a rust inhibitor, a crosslinking agent, a silane coupling agent, a defoaming agent, a stabilizer, etc. may be contained within a range that does not impair the desired properties. In addition, it is preferred to contain a solvent so that the viscosity of the positive photosensitive resin composition can be adjusted to a desired range.
[0064] As the photosensitizer (dissolution inhibitor), substances exemplified as the photosensitizer (dissolution inhibitor) contained in the positive photosensitive composition in International Publication No. 2018 / 168325 can be mentioned.
[0065] The content of the photosensitizer (dissolution inhibitor) in the positive photosensitive resin layer is preferably 5 to 25% by mass.
[0066] As the alkali-soluble resin, for example, resins having hydroxyl groups and / or carboxyl groups can be cited, and preferably (b) resins having phenolic hydroxyl groups. By including (b) a resin having a phenolic hydroxyl group, when a quinonediazide compound is used as a photosensitizer (dissolution inhibitor), the phenolic hydroxyl group forms a hydrogen bond with the quinonediazide compound, which can further suppress the occurrence of loss of the developing film and development peeling of the unexposed part of the positive photosensitive resin layer, making it difficult to visually recognize the opaque wiring electrode pattern. As (b) a resin having a phenolic hydroxyl group, for example, Novolac resins such as phenol Novolac resins and cresol Novolac resins, polymers of monomers having phenolic hydroxyl groups, copolymers with styrene, acrylonitrile, acrylic acid monomers, etc. can be cited. Two or more of them can be contained.
[0067] Examples of the monomer having a phenolic hydroxyl group include 4-hydroxystyrene and hydroxyphenyl (meth)acrylate.
[0068] Among these, (b-1) acrylic resin having a phenolic hydroxyl group and a carboxyl group (hereinafter, sometimes referred to as "(b-1) resin") and (b-2) phenol Novolac resin (hereinafter, sometimes referred to as "(b-2) resin") are preferred.
[0069] In the light-shielding pattern forming step described later, as a developer used in the developing step, the developer exemplified below can be cited. In recent years, development based on sodium carbonate aqueous solution is sometimes required from the viewpoint of safety, because the alkali concentration changes with time during development compared with strong alkaline developers such as tetramethylammonium hydroxide aqueous solution and potassium hydroxide aqueous solution. Compared with other developers such as tetramethylammonium hydroxide aqueous solution, sodium carbonate aqueous solution tends to have lower developability. By containing the (b-1) resin, the developability in the sodium carbonate aqueous solution with a small concentration change with time can be improved.
[0070] The weight average molecular weight of the resin (b-1) is preferably 9,000 to 13,000. From the viewpoint of solubility in a developer, the acid value of the resin (b-1) is preferably 30 to 250 mgKOH / g.
[0071] It is preferred to contain (b-1) resin and (b-2) resin. By also containing (b-2) resin, the positive photosensitive resin layer is easily softened by heating and can be transferred at low temperature, so that the strain of the transparent substrate caused by heat can be suppressed. In addition, when using sodium carbonate aqueous solution as a developer, since the developability of (b-2) resin is lower than that of (b-1) resin, the solubility in the developer can be adjusted.
[0072] From the viewpoint of transferring at a lower temperature, the weight average molecular weight of the (b-2) resin is preferably 100 to 1,500. On the other hand, from the viewpoint of appropriately reducing the solubility in the developer, the weight average molecular weight of the (b-2) resin is preferably 3,000 to 15,000. Two or more (b-2) resins having different weight average molecular weights may be contained.
[0073] From the viewpoint of improving the developability in aqueous sodium carbonate solution, the mass ratio of the content of the resin (b-1) to the content of the resin (b-2) ((b-1) / (b-2)) is preferably 1.0 or more. On the other hand, from the viewpoint of performing transfer at a lower temperature, the mass ratio ((b-1) / (b-2)) is preferably 3.0 or less.
[0074] The content of the alkali-soluble resin in the positive photosensitive resin layer is preferably 45 to 65% by mass.
[0075] The positive photosensitive resin composition preferably further contains a benzotriazole compound. By containing the benzotriazole compound, the transferability of the positive photosensitive resin layer to the opaque wiring electrode pattern is further improved. In addition, the corrosion and ion migration of the metal contained in the opaque wiring electrode pattern can be suppressed. Among the benzotriazole compounds, carboxybenzotriazole is preferred from the viewpoint of improving the transferability and the aspect of less volatilization in the heating process.
[0076] As the solvent, for example, the solvents exemplified as the solvents contained in the positive photosensitive composition in International Publication No. 2018 / 168325 can be mentioned.
[0077] As a method for coating the positive photosensitive resin composition on the release film, for example, spin coating using a spinner, spray coating, roll coating, screen printing, or coating using a slit coater, a knife coater, a die coater, a calender coater, a meniscus coater or a rod coater, etc. The coating thickness of the positive photosensitive resin composition is preferably set so that the thickness T1 of the positive photosensitive resin layer after drying is within the preferred range described below.
[0078] When the positive photosensitive resin composition contains a solvent, it is preferably dried by heating. The drying temperature is preferably 60 to 120° C., and the drying time is preferably 1 to 20 minutes. As the heating drying apparatus, for example, an oven, a hot plate, etc. are preferred.
[0079] From the perspective of making it more difficult to visually identify the opaque wiring electrode pattern, the thickness T1 [μm] of the positive photosensitive resin layer is preferably 0.3 or more, and more preferably 0.5 or more. On the other hand, from the perspective of reducing the development time and further improving the processability, T1 [μm] is preferably 2.0 or less. It should be noted that the thickness T1 [μm] of the positive photosensitive resin layer is obtained by measuring the thickness at 5 randomly selected locations using a stylus step gauge and calculating the average value.
[0080] In addition, it is preferred that the total of the thickness T1 [μm] of the positive photosensitive resin layer and the thickness T2 [μm] of the opaque wiring electrode pattern is 1.5 to 10.0, and T1 and T2 satisfy the following formula (1).
[0081] 0.1 <T1 / (T1+T2)<0.5 (1)
[0082] By making the sum of T1 [μm] and T2 [μm] greater than or equal to 1.5 and satisfying the above formula (1), the conductivity can be further improved, and the opaque wiring electrode pattern is less likely to be visually recognized. The sum of T1 [μm] and T2 [μm] is more preferably greater than or equal to 2.0. On the other hand, by making the sum of T1 [μm] and T2 [μm] less than or equal to 10.0 and satisfying the above formula (1), when the substrate with wiring electrodes has an outer covering layer, the uneven step difference on the transparent substrate can be reduced, and the generation of bubbles caused by the step difference when the outer covering layer is stacked can be suppressed. The sum of T1 [μm] and T2 [μm] is more preferably less than or equal to 5.0, and more preferably less than or equal to 3.5.
[0083] The light-shielding layer is formed by transferring a positive photosensitive resin layer containing a light-shielding component to the opaque wiring electrode pattern forming surface of a transparent substrate. As a transfer method, for example, a method of hot-pressing the dry film obtained by the above method in such a way that the positive photosensitive resin layer is in contact with the above-mentioned transparent substrate can be cited. From the viewpoint of improving transferability, the hot-pressing temperature is preferably above 70°C, and more preferably above 100°C. On the other hand, from the viewpoint of suppressing the deactivation of the photosensitive agent (dissolution inhibitor) caused by heat, the hot-pressing temperature is preferably below 150°C. For example, in order to ensure conduction with external components such as a pad portion and a terminal portion and to expose the opaque wiring electrode pattern, the light-shielding layer may not be transferred. In addition, the light-shielding layer may not be transferred to the opaque wiring electrode pattern opening. By not transferring the transfer layer to the opaque wiring electrode pattern opening, the time required for the development of the light-shielding layer can be further shortened, and the processability can be further improved.
[0084] Next, the release film is peeled off as necessary. When exposure is performed via the release film in the light-shielding pattern forming step described later, the release film may be peeled off after the exposure.
[0085] Next, in the light shielding pattern forming step, the light shielding layer is exposed and developed using the opaque wiring electrode pattern as a mask, thereby forming a light shielding pattern at a location corresponding to the opaque wiring electrode pattern. By exposing the opaque wiring electrode pattern as a mask, a corresponding light shielding pattern can be formed at a location corresponding to the opaque wiring electrode pattern without the need for an additional exposure mask. When the opaque wiring electrode pattern forming step includes a step of forming a first opaque wiring electrode pattern on a single surface of a transparent substrate, a step of forming an insulating layer on the first opaque wiring electrode pattern, and a step of forming a second opaque wiring electrode pattern on the insulating layer, it is preferred that the light shielding pattern is formed at locations corresponding to the first opaque wiring electrode pattern and the second opaque wiring electrode pattern.
[0086] The exposure is preferably performed from the side opposite to the light shielding layer forming side, regardless of the side on which the opaque wiring electrode pattern is formed. In addition, for example, when it is necessary to ensure conduction with external components such as a pad portion or a terminal portion, or to remove the light shielding layer in a portion where the opaque wiring electrode pattern is to be exposed, exposure can be performed from the side on which the light shielding layer is formed using an exposure mask.
[0087] The exposure light preferably emits light in the ultraviolet region that is consistent with the absorption wavelength of the photosensitizer (dissolution inhibitor) contained in the light-shielding layer, that is, in the wavelength region of 200 nm to 450 nm. As a light source for obtaining such exposure light, for example, a mercury lamp, a halogen lamp, a xenon lamp, an LED lamp, a semiconductor laser, a KrF or ArF excimer laser, etc. can be cited. Among these, the i-line (wavelength 365 nm) of the mercury lamp and the LED lamp are preferred. The exposure light can be irradiated while the substrate is left stationary, or it can be irradiated while the substrate is transported in the direction opposite to the surface on which the light-shielding layer is formed in the light source.
[0088] By developing the exposed light-shielding layer, the exposed portion can be removed, and a light-shielding pattern can be formed in a portion corresponding to the opaque wiring electrode pattern.
[0089] As a developer, a developer that does not hinder the conductivity of the opaque wiring electrode pattern is preferred, preferably an alkaline developer. As an alkaline developer, for example, a substance exemplified as a developer in International Publication No. 2018 / 168325 can be cited. As mentioned above, in recent years, it is preferred to use a sodium carbonate aqueous solution that is highly safe and has a small change in alkali concentration over time during development.
[0090] As the developing method, for example, there can be mentioned: a method of spraying a developing solution on the surface of the light-shielding layer while leaving the substrate still or rotating; a method of immersing the light-shielding layer in a developing solution; a method of applying ultrasonic waves while immersing the light-shielding layer in a developing solution; and the like.
[0091] The light shielding pattern obtained by the development process can be subjected to a rinsing treatment based on a rinsing liquid. As the rinsing liquid, for example, the substances exemplified as rinsing liquids in International Publication No. 2018 / 168325 can be cited.
[0092] The obtained light-shielding pattern can be further heated at 100° C. to 300° C. By heating, the hardness of the light-shielding pattern can be improved, defects and peeling caused by contact with other components can be suppressed, and the adhesion with the opaque wiring electrode pattern can be improved. As a heating method, for example, heating using an oven, an inert oven, a heating plate, heating using electromagnetic waves such as an infrared heater, etc. can be cited.
[0093] There may be a step of forming an overcoat on the shading pattern of the obtained substrate with wiring electrodes. As the overcoat, an insulating layer, an adhesive layer having adhesiveness, etc. may be cited. They may be stacked in two or more layers. As a method for forming an insulating layer, for example, the method exemplified in International Publication No. 2018 / 168325 may be cited. As a method for forming an adhesive layer, for example, a method of attaching a transparent adhesive film to a shading pattern using a rubber roller, etc. may be cited.
[0094] Next, a black transfer film preferably used as a dry film in the step of forming a light shielding layer by transferring a positive photosensitive resin layer in the method for producing a substrate with wiring electrodes of the present invention will be described.
[0095] The black transfer film has a positive photosensitive resin layer containing (a) a black pigment, (b) a resin having a phenolic hydroxyl group, and (c) a quinonediazide compound on a releasable film.
[0096] Examples of the release film include the films exemplified as the release film in the light shielding layer forming step using a dry film in the aforementioned method for producing a substrate with wiring electrodes of the present invention.
[0097] Examples of the positive photosensitive resin layer include those exemplified as the positive photosensitive resin layer in the method for producing a substrate with wiring electrodes of the present invention described above.
[0098] (a) The black pigment may be an organic pigment or an inorganic pigment. Examples of organic pigments include soluble azo pigments, insoluble azo pigments, metal complex salt azo pigments, phthalocyanine pigments, condensed polycyclic pigments, and the like. Examples of inorganic pigments include carbon black, graphite, pine soot, or iron oxides such as iron black, hematite, goethite, and magnetite, titanium, chromium, lead, and metal composites thereof. Two or more of these may be contained. The content of the black pigment in the positive photosensitive resin layer is preferably 5 to 30% by mass.
[0099] The (b) resin having a phenolic hydroxyl group is preferably the above-mentioned (b-1) resin and (b-2) resin, and the preferred range of the mass ratio of the content thereof is also as described above.
[0100] The thickness T1 [μm] of the positive photosensitive resin layer is preferably 0.3 or more, and more preferably 0.5 or more, from the viewpoint of making it more difficult to visually recognize the opaque wiring electrode pattern in the method for manufacturing a substrate with wiring electrodes. On the other hand, from the viewpoint of reducing the development time and further improving the processability in the method for manufacturing a substrate with wiring electrodes, T1 [μm] is preferably 2.0 or less.
[0101] Example
[0102] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited thereto.
[0103] The materials used in each example are as follows: The transmittance of the transparent substrate at a wavelength of 365 nm was measured using an ultraviolet visible spectrophotometer (U-3310: manufactured by Hitachi High-Technologies Corporation).
[0104] (Production Example 1: Acrylic resin having a carboxyl group)
[0105] 150 g of diethylene glycol monoethyl ether acetate (hereinafter referred to as "DMEA") was added to a reaction container in a nitrogen atmosphere, and the temperature was raised to 80°C using an oil bath. A mixture containing 20 g of ethyl acrylate (hereinafter referred to as "EA"), 40 g of 2-ethylhexyl methacrylate (hereinafter referred to as "2-EHMA"), 20 g of styrene (hereinafter referred to as "St"), 15 g of acrylic acid (hereinafter referred to as "AA"), 0.8 g of 2,2'-azobisisobutyronitrile and 10 g of DMEA was added dropwise over 1 hour. After the addition was completed, the mixture was further stirred for 6 hours to perform a polymerization reaction. Then, 1 g of hydroquinone monomethyl ether was added to terminate the polymerization reaction. Next, a mixture containing 5 g of glycidyl methacrylate (hereinafter referred to as "GMA"), 1 g of triethylbenzylammonium chloride and 10 g of DMEA was added dropwise over 0.5 hours. After the addition was completed, the mixture was further stirred for 2 hours to perform an addition reaction. The obtained reaction solution was purified with methanol to remove unreacted impurities, and then vacuum dried for 24 hours to obtain a carboxyl-containing acrylic resin having a copolymerization ratio (weight basis): EA / 2-EHMA / St / GMA / AA=20 / 40 / 20 / 5 / 15. The acid value of the obtained carboxyl-containing acrylic resin was measured according to JIS K 0070 (1992) and was 103 mgKOH / g. The weight average molecular weight of the obtained carboxyl-containing acrylic resin was 17,000.
[0106] (Production Example 2: Acrylic resin having phenolic hydroxyl groups and carboxyl groups)
[0107] In a reaction vessel in a nitrogen atmosphere, 150 g of 2-methoxy-1-methylethyl acetate (hereinafter referred to as "PMA") was added and the temperature was raised to 80°C using an oil bath. A mixture containing 20 g of EA, 20 g of 2-EHMA, 20 g of 4-hydroxystyrene (hereinafter referred to as "HS"), 15 g of N-hydroxymethyl acrylamide (hereinafter referred to as "MAA"), 25 g of AA, 0.8 g of 2,2'-azobisisobutyronitrile and 10 g of PMA was added dropwise over 1 hour. After the addition was completed, the mixture was further heated and stirred at 80°C for 6 hours to perform a polymerization reaction. Then, 1 g of hydroquinone monomethyl ether was added to terminate the polymerization reaction. The obtained reaction solution was purified with methanol to remove unreacted impurities, and further vacuum dried for 24 hours to obtain an acrylic resin having a phenolic hydroxyl group and a carboxyl group with a copolymerization ratio (weight basis): EA / 2-EHMA / HS / MAA / AA=20 / 20 / 20 / 15 / 25. The acid value was measured in the same manner as in Production Example 1 and found to be 153 mgKOH / g. The weight average molecular weight of the obtained acrylic resin having a phenolic hydroxyl group and a carboxyl group was 10,000.
[0108] (Production Example 3: Photosensitive Conductive Paste (D-1))
[0109] In a 100 mL clean bottle, 17.5 g of the acrylic resin having a carboxyl group obtained in Manufacturing Example 1, 0.5 g of the photopolymerization initiator N-1919 (manufactured by ADEKA Corporation), 1.5 g of the epoxy resin "ADEKA RESIN (registered trademark)" EP-4530 (epoxy equivalent 190, manufactured by ADEKA Corporation), 3.5 g of the diacrylate "Light Acrylate (registered trademark)" BP-4EA (manufactured by Kyoeisha Chemical Co., Ltd.) and 19.0 g of DMEA were added, and mixed using "Awatori Rentaro (registered trademark)" ARE-310 (manufactured by THINKY Corporation) to obtain 42.0 g of a resin solution. 42.0 g of the obtained resin solution was mixed with 62.3 g of Ag particles having an average particle size of 0.3 μm, and kneaded using a three-roll mill EXAKT M50 (manufactured by EXAKT), and then 7 g of DMEA was added and mixed to obtain 111.3 g of a photosensitive conductive paste (D-1). The viscosity of the obtained photosensitive conductive paste (D-1) was measured using a Brookfield viscometer at a temperature of 25° C. and a rotation speed of 3 rpm, and the result was 10,000 mPa·s.
[0110] (Production Example 4: Photosensitive Conductive Paste (D-2))
[0111] In a 100 mL clean bottle, 3.0 g of the acrylic resin having a carboxyl group obtained in Production Example 1, 0.3 g of a photopolymerization initiator N-1919 (manufactured by ADEK Corporation), 1.2 g of a diacrylate “Light Acrylate (registered trademark)” BP-4EA, 0.5 g of a dispersant “BYK (registered trademark)”-LP21116 (manufactured by BYK-Chemie Co., Ltd.), 79.0 g of propylene glycol monomethyl ether acetate (hereinafter referred to as “PGMEA”), and 16.0 g of silver fine particles having an average surface carbon coating layer thickness of 1 nm and a particle diameter of 40 nm (manufactured by Nisshin Engineering Co., Ltd.) were added, and mixed using “Awatori Rentaro (registered trademark)” ARE-310 (manufactured by THINKY Corporation) to obtain 100.0 g of a photosensitive conductive paste (D-2). The viscosity of the obtained photosensitive conductive paste (D-2) was measured using an E-type viscometer under the conditions of a temperature of 25° C. and a rotation speed of 100 rpm. The result was 3 mPa·s.
[0112] (Production Example 5: Quinonediazide compound)
[0113] Under a dry nitrogen stream, 21.22 g (0.05 mol) of α,α-bis(4-hydroxyphenyl)-4-(4-hydroxy-α,α-dimethylbenzylethylbenzene (trade name TrisP-PA, manufactured by Honshu Chemical Industry Co., Ltd.) and 33.58 g (0.125 mol) of naphthoquinonediazide-5-sulfonyl chloride were dissolved in 450 g of 1,4-dioxane and the mixture was brought to room temperature. 15.18 g of triethylamine mixed with 50 g of 1,4-dioxane was added dropwise so that the temperature in the system did not exceed 35°C. After the addition, the mixture was stirred at 30°C for 2 hours. The triethylamine salt was filtered and the filtrate was poured into water. Then, the precipitate was collected by filtration. The precipitate was dried with a vacuum dryer to obtain a quinonediazide compound.
[0114] (Production Example 6: Positive photosensitive resin composition (E-1))
[0115] In a 100 mL clean bottle, 3.42 g of phenol Novolac resin WR-104 (manufactured by DIC Corporation, weight average molecular weight: 6900), 0.88 g of the quinonediazide compound obtained in Production Example 5, 0.17 g of a crosslinking agent "NIKALAC (registered trademark)" MW-390 (manufactured by Sanwa Chemical), 0.22 g of carboxybenzotriazole "VERZONE (registered trademark)" C-BTA (manufactured by Yamato Chemical Co., Ltd.), 0.01 g of a leveling agent "BYK (registered trademark)" -331 (manufactured by BYK-Chemie), and 44.20 g of PGMEA were added, and mixed using a rotation-revolution vacuum mixer "Awatori Rentaro (registered trademark)" ARE-310 (manufactured by THINKY Corporation) to obtain 48.90 g of a resin solution. 48.90 g of the obtained resin solution, 0.66 g of carbon black MA100 (manufactured by Mitsubishi Chemical Corporation), and 0.44 g of dispersant "BYK"-LP21116 (manufactured by BYK-Chemie) were mixed, and kneaded using an Ultra Apex Mill (manufactured by Kotobuki Industry Co., Ltd.) equipped with a centrifugal separator filled with 70 volume % of 0.05 mmφ zirconium oxide beads (manufactured by Toray Industries, Ltd.) to obtain 50.0 g of a positive photosensitive resin composition (E-1).
[0116] (Production Example 7: Positive photosensitive resin composition (E-2))
[0117] A positive photosensitive resin composition (E-2) was obtained in the same manner as in Production Example 6, except that 3.42 g of phenol Novolac resin WR-104 (manufactured by DIC Corporation) was replaced with 2.54 g of phenol Novolac resin WR-104 (manufactured by DIC Corporation) and 0.88 g of the acrylic resin having a phenolic hydroxyl group and a carboxyl group obtained in Production Example 2.
[0118] (Production Example 8: Positive photosensitive resin composition (E-3))
[0119] A positive photosensitive resin composition (E-3) was obtained in the same manner as in Production Example 6, except that 3.42 g of phenol Novolac resin WR-104 (manufactured by DIC Corporation) was replaced with 2.10 g of phenol Novolac resin WR-104 (manufactured by DIC Corporation) and 1.31 g of the acrylic resin having a phenolic hydroxyl group and a carboxyl group obtained in Production Example 2.
[0120] (Production Example 9: Positive photosensitive resin composition (E-4))
[0121] A positive photosensitive resin composition (E-4) was obtained in the same manner as in Production Example 6, except that 3.42 g of phenol Novolac resin WR-104 (manufactured by DIC Corporation) was replaced with 2.84 g of phenol Novolac resin WR-104 (manufactured by DIC Corporation) and 0.58 g of the acrylic resin having a phenolic hydroxyl group and a carboxyl group obtained in Production Example 2.
[0122] (Production Example 10: Positive photosensitive resin composition (E-5))
[0123] A positive photosensitive resin composition (E-5) was obtained in the same manner as in Production Example 6, except that 3.42 g of phenol Novolac resin WR-104 (manufactured by DIC Corporation) was replaced with 1.55 g of phenol Novolac resin WR-104 (manufactured by DIC Corporation) and 1.86 g of the acrylic resin having a phenolic hydroxyl group and a carboxyl group obtained in Production Example 2.
[0124] (Production Example 11: Positive photosensitive resin composition (E-6))
[0125] A positive photosensitive resin composition (E-6) was obtained in the same manner as in Production Example 6 except that 3.42 g of the phenol Novolac resin WR-104 (manufactured by DIC Corporation) was replaced with 3.42 g of the acrylic resin having a phenolic hydroxyl group and a carboxyl group obtained in Production Example 2.
[0126] Evaluations in each of the Examples and Comparative Examples were performed by the following methods.
[0127] (1) Thickness of positive photosensitive resin layer
[0128] For the positive photosensitive resin layer of the black transfer film obtained in Reference Examples 1 to 11, the thickness was measured at 5 randomly selected locations using a stylus-type step difference meter "SURFCOM" (registered trademark) 1400 (manufactured by Tokyo Seimitsu Co., Ltd.), and the average value was calculated. For Comparative Examples 1 and 3, in the <Light-shielding layer forming step>, the light-shielding layer formed on the opaque wiring electrode pattern was observed in cross section using SEM, and the thickness was measured at 5 randomly selected locations, and the average value was calculated.
[0129] (2) Thickness, line width, and light transmittance of the opaque wiring electrode pattern
[0130] For the cured opaque wiring electrode pattern formed in the <opaque wiring electrode pattern forming process> in Examples 1 to 16 and Comparative Examples 1 to 4, the thickness was measured at 5 randomly selected locations using a stylus-type step difference meter "SURFCOM" (registered trademark) 1400 (manufactured by Tokyo Seimitsu Co., Ltd.), and the average value was calculated. In addition, the line width of the fine line pattern portion at 5 randomly selected locations was measured using an optical microscope, and the average value was calculated. In Examples 2 and 9, the pattern was measured after rinsing. In addition, for Figure 4 The light transmittance at wavelengths of 365 nm and 550 nm was measured at a portion corresponding to the pad portion 6 of the pattern shown for evaluation of visibility and conductivity using a micro-spectrophotometer (VSS 400: manufactured by Nippon Denshoku Industries Co., Ltd.).
[0131] (3) Developability
[0132] The positive photosensitive resin layers exposed in the <light shielding pattern forming step> in Examples 1 to 16 and Comparative Examples 1 and 3 were developed using a 2.38 mass % tetramethylammonium hydroxide (TMAH) aqueous solution as a developer to measure the time required to completely expose the transparent substrate in the exposed portion.
[0133] (4) Exposure sensitivity
[0134] In the <light shielding pattern forming step> in Examples 1 to 16 and Comparative Examples 1 to 4, the development time using a 2.38 mass % TMAH aqueous solution was set to 50 seconds, and the exposure sensitivity was evaluated using the minimum exposure amount that could dissolve the photosensitive resin layer in the exposed portion.
[0135] (5) Sodium carbonate development
[0136] In the developability evaluation of (3) above, a 5.0 mass % sodium carbonate aqueous solution was used as a developer instead of a 2.38 mass % TMAH aqueous solution, and the time required for the transparent substrate of the exposed part to be completely exposed was measured. However, if the transparent substrate was not completely exposed within 180 seconds, it was evaluated as "NG".
[0137] (6) Visual recognition difficulty
[0138] For the substrates with wiring electrodes obtained from Examples 1 to 16 and Comparative Examples 1 to 4, a black film was provided on the side opposite to the surface on which the opaque wiring electrode pattern was formed, and then light was projected onto the substrates with wiring electrodes using a light projector. Ten people visually observed the substrates from a distance of 30 cm to evaluate whether the grid-shaped electrode portion could be visually recognized. The visual recognition difficulty was evaluated by the number of people who could visually recognize the electrode portion.
[0139] (7) Electrical conductivity
[0140] The resistance value between the terminals was measured using a resistance measuring tester for the substrates with wiring electrodes obtained in Examples 1 to 16 and Comparative Examples 1 to 4. The distance between the terminals was 17 mm and the width was 15 mm, and the pad portion 6 was 2 mm in length and 15 mm in width.
[0141] (8) Coating processability
[0142] Three transparent adhesive films, namely "LUCIACS (registered trademark)" CS9861UAS (tape thickness 25 μm), "LUCIACS (registered trademark)" CS9862UAS (tape thickness 50 μm), and "LUCIACS (registered trademark)" CS9863UAS (tape thickness 75 μm) (all manufactured by Nitto Denko Corporation), were prepared respectively. After peeling off the carrier film on one side, the films were attached to the opaque wiring electrode pattern-forming surface of the substrate with wiring electrodes obtained in Examples 1 to 16 and Comparative Examples 1 to 4 using a rubber roller. The presence of bubbles was observed using an optical microscope (VHX-6000 manufactured by Keyence Corporation). The case where no bubbles were observed in all three cases was evaluated as "A", the case where bubbles were observed in one case was evaluated as "B", and the case where bubbles were observed in two or more cases was evaluated as "C".
[0143] (9) Transferability
[0144] The transfer temperature in the <light shielding layer forming step> in Examples 1 to 16 was set to 90° C., 100° C., and 110° C., and the transferability was evaluated based on the lowest transfer temperature at which the film could be transferred onto the opaque wiring electrode pattern without omission.
[0145] (Reference Example 1)
[0146] A non-silicone release agent AL-5 (manufactured by Lintec Co., Ltd.) was applied to one side of a PET film "Lumirror (registered trademark)" FB40 (manufactured by Toray Industries, Ltd.) (thickness: 16 μm), and heat-treated and dried to form a release layer with a thickness of 100 nm on the surface of the substrate to obtain a release film. With respect to the obtained release film, an acrylic adhesive tape "31B" manufactured by Nitto Denko Co., Ltd. was attached to the surface formed with the release layer using a 2 kg roller, and after standing for 30 minutes, the peeling force when peeled off at a peeling angle of 180° and a peeling speed of 0.3 m / min was measured, and the result was 1,480 mN / 20 mm.
[0147] The positive photosensitive resin composition (E-1) obtained in Production Example 6 was applied to the release layer of the obtained release film using a coater so as to have a thickness of 0.7 μm after drying, and dried at 80° C. for 4 minutes to form a positive photosensitive resin layer, thereby obtaining a black transfer film (F-1).
[0148] (Reference Examples 2 to 11)
[0149] Black transfer films (F-2) to (F-11) were obtained in the same manner as in Example 1 except that the type of the positive photosensitive resin composition forming the positive photosensitive resin layer and the thickness of the positive photosensitive resin layer were changed as described in Table 1.
[0150] [Table 1]
[0151] [Table 1]
[0152]
[0153] (Example 1)
[0154] <Opaque Wiring Electrode Pattern Formation Step>
[0155] The photosensitive conductive paste (D-1) obtained in Preparation Example 3 was printed on one side of a PET film "Lumirror (registered trademark)" T60 (manufactured by Toray Industries, Ltd., thickness: 75 μm, transmittance at a wavelength of 365 nm: 77%, transmittance at a wavelength of 550 nm: 89%) by screen printing so that the thickness after drying was 1.6 μm, and dried at 100°C for 10 minutes. Figure 4 The exposure mask having the pad portion 6 and the mesh-shaped fine line pattern portion 7 shown in the figure was exposed at 500 mJ / cm using an exposure device (PEM-6M; manufactured by Union Optical Co., Ltd.). 2 Here, the grid-shaped pattern is Figure 5 The grid pitch P shown is 150 μm, the grid angle θ is 90°, and the negative pattern has an opening portion 9 with an opening width of 4 μm and a light shielding portion 8. Then, immersion development is performed for 30 seconds using a 0.2 mass % sodium carbonate aqueous solution as a developer, and further rinsed with ultrapure water, and then cured in an IR heating furnace at 140°C for 30 minutes to form an opaque wiring electrode pattern. The line width and thickness of the opaque wiring electrode pattern were measured using the aforementioned method, and the results showed that the line width was 6 μm and the thickness was 1.6 μm. In addition, the transmittance at wavelengths of 365 nm and 550 nm was measured using the aforementioned method, and the results were both 1%.
[0156] <Light-shielding layer forming step>
[0157] On the obtained opaque wiring electrode pattern, the black transfer film (F-1) was thermally pressed at 110°C and at a speed of 0.2 m / min in such a way that the positive photosensitive resin layer of the black transfer film (F-1) obtained in Reference Example 1 was in contact with it, and the release film was peeled off.
[0158] <Light-shielding pattern forming step>
[0159] Using the opaque wiring electrode pattern as a mask, an exposure device (PEM-6M) was used to expose the film at an exposure dose (converted to a wavelength of 365 nm) of 100 J / cm from the side opposite to the surface on which the opaque wiring electrode pattern was formed. 2 、300J / cm 2 , 500J / cm 2 、1,000J / cm 2 , 2,000J / cm 2 , 4,000mJ / cm 2 Then, through an exposure mask that shielded the area other than the area corresponding to the pad portion of the opaque wiring electrode pattern, an exposure device (PEM-6M) was used to expose the positive photosensitive dry film transfer surface at 500 mJ / cm 2 The exposed substrate was exposed to light with an exposure amount of 1.50 % (converted to a wavelength of 365 nm). Then, a 2.38 mass % TMAH aqueous solution was used as a developer until the transparent substrate of the exposed part was exposed, and a light shielding pattern was formed on the upper part of the opaque wiring electrode pattern. The substrate was further heated in a box oven at 140° C. for 60 minutes to obtain a substrate with wiring electrodes.
[0160] (Example 2)
[0161] <Opaque Wiring Electrode Pattern Formation Step>
[0162] A copper film with a thickness of 2.5 μm was formed on one side of a PET film "Lumirror (registered trademark)" T60 (manufactured by Toray Industries, Ltd.) by vapor deposition. Then, a resist LC-140 (manufactured by Rohm and Haas Electronic Materials, Ltd.) was applied on the copper film by spin coating and dried at 100°C for 5 minutes. Figure 4 The exposure mask having the pad portion 6 and the mesh-shaped fine line pattern portion 7 shown in the figure was exposed at 45 mJ / cm using an exposure device (PEM-6M; manufactured by Union Optical Co., Ltd.). 2 Here, the grid-shaped pattern is Figure 6The grid pitch P shown is 150μm, the grid angle θ is 90°, and the positive pattern has an opening 9 and a shading portion 8 with a shading width of 16μm. Then, immersion development is performed for 30 seconds using a 2.38% by mass TMAH aqueous solution as a developer, and further rinsed with ultrapure water for 30 seconds. Next, an aqueous solution of ferric chloride is used to etch in a manner such that the line width becomes 6μm, and further rinsed with ultrapure water for 30 seconds. Next, immersion development is performed for 4 minutes using the resist stripping solution JELK-101 (manufactured by Kanto Chemical Co., Ltd.), and further rinsed with ultrapure water for 30 seconds to form an opaque wiring electrode pattern. The line width and thickness of the opaque wiring electrode pattern were measured using the aforementioned method, and the results showed that the line width was 4μm and the thickness was 2.5μm. In addition, the transmittance at wavelengths of 365nm and 550nm was measured using the aforementioned method, and the results were both 0%.
[0163] The <light shielding layer forming step> and the <light shielding pattern forming step> were carried out in the same manner as in Example 1 to obtain a substrate with wiring electrodes.
[0164] (Example 3)
[0165] A substrate with wiring electrodes was obtained in the same manner as in Example 1 except that the opening width of the exposure mask used in the <Opaque wiring electrode pattern forming step> was changed to 10 μm.
[0166] (Example 4)
[0167] <Opaque Wiring Electrode Pattern Formation Step>
[0168] The photosensitive conductive paste (D-2) obtained in Preparation Example 4 was applied to one side of an alkali-free glass "AN Wizus" (registered trademark) (AGC Co., Ltd., transmittance at a wavelength of 365 nm: 91%, transmittance at a wavelength of 550 nm: 92%) by spin coating so as to have a thickness of 1 μm after drying, and dried at 90° C. for 8 minutes. Figure 4 The exposure mask having the pad portion 6 and the mesh-shaped fine line pattern portion 7 shown in the figure was exposed at an exposure dose of 150 mJ / cm using an exposure device (PEM-6M; manufactured by Union Optical Co., Ltd.). 2 (converted to a wavelength of 365nm) for exposure. Here, the grid-shaped pattern is Figure 5The grid pitch P shown is 150 μm, the grid angle θ is 90°, and the negative pattern has an opening portion 9 with an opening width of 6 μm and a shading portion 8. Then, a 0.1 mass % TMAH aqueous solution is used as a developer, and the exposure portion is developed for twice the time of dissolution, and then rinsed with ultrapure water for 30 seconds, and then cured in a box oven at 240°C for 60 minutes to form an opaque wiring electrode pattern. The line width and thickness of the opaque wiring electrode pattern were measured using the above method. As a result, the line width was 6 μm and the thickness was 0.5 μm. In addition, the transmittance at wavelengths of 365 nm and 550 nm was measured using the above method, and the results were both 0%.
[0169] <Light-shielding layer forming step>
[0170] A light shielding layer was formed in the same manner as in Example 1, except that the black transfer film (F-2) obtained in Reference Example 2 was used instead of the black transfer film (F-1) obtained in Reference Example 1 for the formed wiring electrode pattern.
[0171] Regarding the <light shielding pattern forming step>, the same operation as in Example 1 was carried out to obtain a substrate with wiring electrodes.
[0172] (Examples 5, 7-8, 10-11)
[0173] A substrate with wiring electrodes was obtained in the same manner as in Example 1 except that the black transfer film used in the <Light-shielding layer forming step> was changed as described in Tables 2 to 3.
[0174] (Example 6)
[0175] Except having changed the black transfer film used in the <light shielding layer forming step> as described in Table 2, it carried out similarly to Example 4, and obtained the board|substrate with wiring electrode.
[0176] (Example 9)
[0177] Except having changed the black transfer film used in the <light shielding layer forming step> as described in Table 3, it carried out similarly to Example 2, and obtained the board|substrate with wiring electrode.
[0178] (Examples 12 to 16)
[0179] The black transfer film used in the <light-shielding layer forming process> is changed as shown in Tables 3 to 4. In the <light-shielding pattern forming process>, a 5.0 mass % sodium carbonate aqueous solution is used as a developer instead of a 2.38 mass % TMAH aqueous solution. Otherwise, the same operation as in Example 1 is performed to obtain a substrate with wiring electrodes.
[0180] (Comparative Example 1)
[0181] In the <light shielding layer forming step>, the positive photosensitive resin composition (E-1) obtained in Manufacturing Example 6 was applied on the opaque wiring electrode pattern by spin coating so that the thickness of the non-formed portion of the opaque wiring electrode pattern after drying became 2.6 μm, and dried at 100° C. for 10 minutes to form a light shielding layer. The same operation as in Example 1 was performed to obtain a substrate with wiring electrodes. The thickness of the light shielding layer was measured by the above-mentioned method and the result was 1.0 μm.
[0182] (Comparative Example 2)
[0183] A substrate with wiring electrodes was obtained in the same manner as in Example 1 except that the <light shielding layer forming step> and the <light shielding pattern forming step> were not performed.
[0184] (Comparative Example 3)
[0185] In the <light shielding layer forming step>, the positive photosensitive resin composition (E-1) obtained in Manufacturing Example 6 was applied on the opaque wiring electrode pattern by spin coating so that the thickness of the non-formed portion of the opaque wiring electrode pattern after drying was 2.6 μm, and dried at 100° C. for 10 minutes to form a light shielding layer. A substrate with wiring electrodes was obtained in the same manner as in Example 2. The thickness of the light shielding layer was measured by the above-mentioned method and the result was 0.3 μm.
[0186] (Comparative Example 4)
[0187] A substrate with wiring electrodes was obtained in the same manner as in Example 2 except that the <light shielding layer forming step> and the <light shielding pattern forming step> were not performed.
[0188] The evaluation results of each example and comparative example are shown in Tables 2 to 4.
[0189] [Table 2]
[0190]
[0191] [Table 3]
[0192]
[0193] [Table 4]
[0194]
[0195] Description of Reference Numerals
[0196] 1: Transparent substrate
[0197] 2: Opaque wiring electrode pattern
[0198] 3: Shading pattern
[0199] 4: Insulation layer
[0200] 5: Light-shielding layer
[0201] 6: Pad
[0202] 7: Fine line pattern
[0203] P: Grid spacing
[0204] θ: grid angle
[0205] L: Line length
[0206] 8: Shading part
[0207] 9: Opening
Claims
1. A method for manufacturing a substrate with wiring electrodes, comprising: forming an opaque wiring electrode pattern on at least one surface of a transparent substrate; a step of forming a light shielding layer by transferring a positive photosensitive resin layer containing a light shielding component to the opaque wiring electrode pattern forming surface of the transparent substrate; and The light shielding layer is exposed to light using the opaque wiring electrode pattern as a mask and then developed to form a light shielding pattern at a portion corresponding to the opaque wiring electrode pattern.
2. The method for manufacturing a substrate with wiring electrodes according to claim 1, wherein: The thickness T1 [μm] of the positive photosensitive resin layer is 0.3 to 2.
0.
3. The method for manufacturing a substrate with wiring electrodes according to claim 1 or 2, wherein: The total of the thickness T1 [μm] of the positive photosensitive resin layer and the thickness T2 [μm] of the opaque wiring electrode pattern is 1.5 to 10.0, and T1 and T2 satisfy the following formula (1): 0.1 <T1 / (T1+T2)<0.5 (1)。 4. The method for manufacturing a substrate with wiring electrodes according to claim 1 or 2, wherein: The thickness T2 [μm] of the opaque wiring electrode pattern is 1.0 to 5.
0.
5. The method for manufacturing a substrate with wiring electrodes according to claim 1 or 2, wherein: The positive photosensitive resin layer contains (b-1) an acrylic resin having a phenolic hydroxyl group and a carboxyl group.
6. The method for manufacturing a substrate with wiring electrodes according to claim 5, wherein: The positive photosensitive resin layer further contains (b-2) phenol Novolac resin.
7. The method for manufacturing a substrate with wiring electrodes according to claim 6, wherein: The mass ratio ((b-1) / (b-2)) of the content of the (b-1) acrylic resin having phenolic hydroxyl groups and carboxyl groups to the content of the (b-2) phenol Novolac resin in the positive photosensitive resin layer is 1.0 to 3.
0.
8. The method for manufacturing a substrate with wiring electrodes according to claim 1 or 2, wherein: The line width of the opaque wiring electrode pattern is 1 to 10 μm.
9. The method for manufacturing a substrate with wiring electrodes according to claim 1 or 2, wherein: The substrate with wiring electrodes has at least a fine line pattern portion, and in the fine line pattern portion, a region where the opaque wiring electrode pattern is formed accounts for 20% by area or less relative to the entire transparent substrate.
10. The method for manufacturing a substrate with wiring electrodes according to claim 1 or 2, wherein: The light transmittance of the opaque wiring electrode pattern at a wavelength of 365 nm is less than 15%.
11. The method for manufacturing a substrate with wiring electrodes according to claim 1 or 2, wherein: The opaque wiring electrode pattern includes silver and / or copper.
